2005
DOI: 10.1021/ja051669e
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Route to Size-Controlled fcc and fct FePt Nanoparticles

Abstract: We report here a new synthetic route to FePt nanoparticles using a stoichiometric mixture of Na2Fe(CO)4 and Pt(acac)2. The structure of FePt nanoparticles, their size, chemical composition, and magnetic property can be controlled by various synthetic parameters, such as the solvent type, nature, and molar ratio of surfactants and stabilizers, synthesis temperature, and purification process. Partially ordered fct (L10) nanoparticles with room temperature magnetic coercivity can be synthesized directly in tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 22 publications
(12 reference statements)
4
88
0
4
Order By: Relevance
“…Various methods aimed at avoiding sintering have been reported, such as rapid thermal annealing, [2] in-situ thermal annealing, [3] preannealing of surfactant, [4] inert coatings followed by annealing, [5] epitaxial growth at high temperatures (500°C [6] ) or low temperatures (230°C [7] ), metal additives for the reduction of the ordering temperature, [8] covalent bonding with the substrate, [9] salt matrix annealing, [10] and direct L1 0 production in high boiling point solvents. [11] Another problem associated with annealing is incomplete phase transformation due to the dependence of the transformation temperature on particle size. Several workers have suggested that FePt does not order below a critical size of 3 nm in nanoparticles and 4 nm in granular thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods aimed at avoiding sintering have been reported, such as rapid thermal annealing, [2] in-situ thermal annealing, [3] preannealing of surfactant, [4] inert coatings followed by annealing, [5] epitaxial growth at high temperatures (500°C [6] ) or low temperatures (230°C [7] ), metal additives for the reduction of the ordering temperature, [8] covalent bonding with the substrate, [9] salt matrix annealing, [10] and direct L1 0 production in high boiling point solvents. [11] Another problem associated with annealing is incomplete phase transformation due to the dependence of the transformation temperature on particle size. Several workers have suggested that FePt does not order below a critical size of 3 nm in nanoparticles and 4 nm in granular thin films.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, a 1 : 1 molar ratio of platinum acetylacetonate to Na 2 Fe(CO) 4 , and a surfactant oleylamine are sonicated and then refluxed in tetracosane at 389°C under an inert atmosphere. Magnetic measurements of samples produced directly in solution show a coercivity of 1300 Oe at 290 K and 3100 Oe at 10 K. [53] Monodisperse CoPt 3 nanocrystals are synthesized via simultaneous reduction of platinum acetylacetonate and thermodecomposition of cobalt carbonyl in different coordinating mixtures in the presence of 1-adamantanecarboxylic acid. The average particle size can be varied from 1.5 to 7.2 nm by controlling reaction conditions and types of coordinating mixture.…”
Section: Metalsmentioning
confidence: 99%
“…Since 2000, great efforts have been made to produce monodisperse fct FePt nanoparticles [2][3][4][5][6][7][8] driven by potential applications of the magnetically anisotropic nanoparticles in high-density recording media and high-performance nanocomposite magnets. Recently, we obtained monodisperse fct FePt nanoparticles with retained size and shape by using salts as the annealing separating media.…”
Section: Introductionmentioning
confidence: 99%